High Strain‐Rate Compression Experiments on Ni/Polyurethane Hybrid Metal Foams Using the Split‐Hopkinson Pressure Bar Technique. Issue 3 (11th November 2021) - Felten, Markus; Fries, Michael; Fíla, Tomáš; Zlámal, Petr; Falta, Jan; Jiroušek, Ondřej; Jung, Anne
Abstract : Open‐cell metal foams are a versatile class of porous lightweight materials, which are predominantly used as kinetic energy absorbers in a wide scope of applications. Based on their bio‐inspired inhomogeneous 3D porous structure, they are capable to significantly reduce the mass of structural designs. Starting with a polyurethane (PU) template foam, the specimens in the present contribution are manufactured by an electrochemical nickel (Ni) deposition. This manufacturing process is beneficial regarding both the specimen design and the adjustment of mechanical properties correlated with the Ni‐coating thickness. Herein, the strain‐rate sensitivity of open‐cell Ni/PU hybrid metal foams is investigated by quasistatic compression tests and high‐velocity impact tests conducted with a conventional split‐Hopkinson pressure bar device. Abstract : The strain‐rate sensitivity of open‐cell Ni/polyurethane hybrid metal foams is investigated by quasistatic and high‐velocity impact experiments. The normalized plastic collapse stress as well as the energy absorption capacity exhibit a distinct strain‐rate sensitivity depending on the specimen size. Furthermore, a second strain‐rate effect is observed during progressive dynamic strain.